Method for modifying plugging material
By self-assemblying graphene oxide and polymer on the surface of the plugged material, the problems of insufficient swelling and temperature resistance of existing materials in high temperature and oil-based drilling fluid are solved, and better blocking effect and stability are achieved sex.
Patent Information
- Application Number
- CN202310736224.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-20
AI Technical Summary
Existing leak plugging materials are prone to swelling in high temperature and oil-based drilling fluid, resulting in unsatisfactory leak plugging effect and insufficient temperature and oil resistance, which cannot effectively solve complex types of leak problems.
Graphene oxide and polymer self-assembly technology are used to form a composite film on the surface of the leak-blocking material to improve its hydrophobicity, temperature resistance and mechanical properties, and form a deposition layer with an orderly structure to enhance the leak-blocking effect.
The modified leak plugging material remains stable at high temperatures, is not easy to swell, has good oil resistance and dispersion, and can effectively plug various types of leaks, improve the success rate of leak plugging, and avoid repeated leaks.
Smart Images

Figure CN119161861A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of petroleum drilling materials, in particular to a plugging agent for oil-based drilling fluid leakage. Background Art
[0002] Well leakage is the phenomenon that various working fluids leak into the formation under the action of pressure difference during various downhole operations such as drilling, cementing completion, testing or well repair. Once well leakage occurs, it will not only delay drilling time, lose drilling fluid, damage oil and gas layers, interfere with geological logging work, increase drilling costs, but also easily cause a series of complex situations such as drill sticking, blowout, well collapse, and even lead to the scrapping of the wellbore, causing huge economic losses.
[0003] With the further understanding of the causes of different well leakage, the research and development of plugging materials is also constantly improving. When a well leak occurs, the compound ratio of granular, flaky and fibrous plugging materials is generally adjusted according to the different pore sizes and positions of the leakage layer, and appropriate inert materials are added to complement them to enhance the plugging effect. Commonly used granular plugging materials include walnut shells, rubber particles, diatomaceous earth, asphalt, etc.; fibrous materials include sawdust, cotton fiber, flax fiber, etc.; sheet materials include mica flakes, rice husks, etc. During the drilling process, artificial cracks caused by fast drilling speed or fast drilling can be plugged by using the non-solidified characteristics of soft and hard plugging materials to form non-flowing viscous substances. Such materials mainly include diesel bentonite slurry, shear thickening liquid, barite plug and lime milk. The above types of plugging materials can solve partial leakage and loss-return leakage caused by pores and cracks, but some complex leakage cannot be solved well. Therefore, various new plugging agents such as chemical plugging agents, high water loss plugging agents, mixed plugging slurries, etc. have emerged, providing effective means to deal with various types of well leakage and improve the success rate of well leakage treatment.
[0004] With the continuous advancement of technology, various targeted plugging materials have been developed, including high water loss plugging materials, chemical plugging materials, mixed plugging thick slurry, etc. After the high water loss plugging material slurry enters the leakage layer, it quickly loses water to form a filter cake under the pressure difference generated by the drilling fluid column pressure and the bottom pressure, plugging the leakage channel. This type of material mainly includes permeable materials, fibrous materials, diatomaceous earth and porous inert materials; chemical plugging materials use the static force, intermolecular force and chemical bond force of polymers on the interface to make the compounds form adhesion at the interface to play a plugging role. This type of material includes gel plugging agents, resin plugging agents, and expansive plugging agents; mixed plugging thick slurry is mainly based on special cement and mixed cement thick slurry, and different admixtures are added to improve the early strength and stability of cement stone, so that it has a higher pressure bearing capacity. These types of plugging materials can play a good plugging role for permeable leakage and fracture leakage. However, with the improvement of drilling technology requirements, vicious leakage such as cave leakage often occurs, and these conventional plugging materials cannot effectively play a plugging role.
[0005] At present, the plugging materials commonly used in plugging construction are mostly bridging plugging materials and chemical gel plugging materials. Chemical plugging mainly plays a plugging role through the chemical reaction of polymers, including cross-linking reaction, curing reaction and other methods. Chemical plugging has a good plugging effect on malignant leakage, but the chemical plugging reaction is more intense, the construction is complex and the risk is higher. Bridging plugging materials have simple construction processes and low costs. They are most commonly used on site, but some materials have poor temperature resistance and are prone to decomposition and failure at high temperatures, resulting in repeated leakage of the leaking layer. At the same time, these materials have problems such as sealing doors and cannot be soaked for a long time, and the plugging effect is sometimes not ideal.
[0006] In the past two decades, researchers have discovered a variety of methods for preparing ultra-thin films through in-depth exploration. In particular, there has been great progress in the field of layer-by-layer self-assembly, which is due to the very good effect of layer-by-layer self-assembly in the innovative design and application of ultra-thin films with special functional properties. For example, invention patent 200710042997.7 proposes a nano-layered calcium carbonate bionic composite material, which is formed by low molecular weight organic matter participating in the reaction process of calcium chloride and sodium carbonate, guiding calcite to form a nano-thin layer structure, and then making the layered structure oriented to assemble a multilayer structure of nano-thin layers. These studies have played an important role in promoting the bionic synthesis of biomineralized materials, but they have not yet grown into bionic materials with natural calcium carbonate structures, or the methods and material performance need to be further improved.
[0007] Some researchers use sponge as a skeleton material with high crack matching properties. For example, invention patent 201410164250.9 "A pressure-bearing plugging agent for oil and gas well drilling and its preparation and application" proposes an oil and gas well drilling pressure-bearing plugging agent, which is composed of a mixture of elastic sponge fiber, oil well cement, ground slag, calcic clay, mica powder and clean water and can be used for oil and gas well drilling pressure plugging.
[0008] At present, sponge materials are prone to swelling in oil-based drilling fluids, which leads to loss of elasticity and greatly reduces the plugging effect. Therefore, it is necessary to modify the sponge to improve its hydrophobicity and temperature and oil resistance. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for modifying a plugging material, wherein the method is to modify the plugging material by coating the plugging material surface with graphene oxide and polymer self-assembly under the action of pressure difference. A thin film is formed on the plugging bridging material mainly through the principle of self-assembly, thereby improving the hydrophobicity, temperature resistance, oil resistance and mechanical properties of the original plugging bridging material, making it have better dispersibility in the drilling fluid, not prone to swelling problems, maintaining better compression elasticity, making it have better matching with the crack, and being conducive to deep cracks. At the same time, the shape can be restored after cracking, which is conducive to the implementation of bridging into a network, and has a good plugging effect for various types of leakage, can better improve the plugging success rate, avoid the occurrence of repeated leakage, and has a good plugging effect for fracture-hole type leakage.
[0010] The modification method of the plugging material of the present invention is to modify the plugging bridging material by coating the plugging material surface with graphene oxide and polymer self-assembly under the action of pressure difference. The hydrophobicity, temperature resistance, oil resistance and mechanical properties of the modified plugging material are improved, the dispersibility in the drilling fluid is good, the swelling problem is not easy to occur in the oil, and the good compression elasticity is maintained, which is conducive to improving the plugging effect.
[0011] The principle of modified membrane formation is the dynamic LbL method, which can force the polyanion membrane-forming solution and the polycation membrane-forming solution to be alternately and dynamically filtered on the surface of the base membrane under a certain pressure. The polyions and polyion complexes are retained by the surface of the support membrane, and the flaky material particles are forced to quickly complete self-assembly in a short time to form a structurally ordered deposition layer, which is a composite membrane.
[0012] The specific plan is as follows:
[0013] A method for modifying a plugging material comprises the steps of using graphene oxide and anionic polymer to self-assemble into a film on the surface of the plugging material.
[0014] Optionally, the modification method comprises:
[0015] (1) Adding graphene oxide to deionized water, stirring, standing, and taking the supernatant to obtain a graphene oxide solution
[0016] (2) adding the anionic polymer in small amounts to deionized water several times, stirring and dissolving, to obtain an anionic polymer solution;
[0017] (3) mixing the graphene oxide solution with the anionic polymer solution to obtain a mixed solution;
[0018] (4) Add plugging materials to the mixed liquid, pressurize, filter out, and dry.
[0019] Optionally, in step (1), the mass ratio of graphene oxide to deionized water is 1-2:100-500.
[0020] Optionally, in step (1), the stirring rate is 1000 to 2000 rpm and the time is 6 to 8 hours.
[0021] Optionally, in step (1), the standing time is 16 to 24 hours.
[0022] Optionally, in step (2), the mass ratio of the anionic polymer to deionized water is 0.05-0.8:50-100.
[0023] Optionally, in step (2), the stirring rate is 1000 to 2000 rpm and the time is 1 to 5 hours.
[0024] Optionally, in step (3), the mass ratio of the graphene oxide solution to the anionic polymer solution is 1:1 to 1:4.
[0025] Optionally, in step (4), the ratio of the mass of the plugging material to the volume of the mixed liquid is (0.1-0.4) g:1 ml, and the plugging material needs to be immersed in the mixed liquid.
[0026] Optionally, in step (4), the pressure after pressurization is 2 to 3 MPa.
[0027] Optionally, in step (4), the filtration time is 5 to 20 minutes.
[0028] Optionally, in step (4), the drying is carried out under natural conditions for 24 to 36 hours.
[0029] Optionally, the plugging material is a granular solid material.
[0030] Optionally, the particle size of the plugging material is 0.5 to 5 mm.
[0031] Optionally, the plugging material is selected from at least one of polyurethane sponge, walnut shells, and rubber particles.
[0032] Optionally, the anionic polymer is selected from at least one of polyacrylic acid and anionic polyacrylamide.
[0033] The present invention also provides a plugging material prepared by the modification method, wherein the plugging material has a graphene oxide and anionic polymer self-assembled composite film layer on its surface.
[0034] The present invention also provides an application of the plugging material prepared by the modification method in preventing leakage of oilfield drilling fluid.
[0035] As a specific embodiment of the present invention, a method for modifying a plugging material comprises the following steps:
[0036] (1) Preparation of GO (graphene oxide) solution: Weigh 1-2 g of GO solid powder, add 100-500 g of deionized water into the mixing cup of a high-speed blender, stir at high speed, add the 1-2 g of GO weighed above into the deionized water in small amounts several times, and set the stirring time to 6-8 h. After stirring, let the GO solution stand for 16-24 h and take the supernatant.
[0037] (2) Preparation of polymer solution: Weigh 0.05-0.8 g of polymer and add it in small amounts to a stirring cup containing 50-100 g of deionized water, and stir at high speed using a high-speed stirrer until it is completely dissolved, thereby obtaining a polymer solution.
[0038] (3) Preparation of mixed solution: The prepared GO solution is mixed with the polymer solution to obtain a mixed solution.
[0039] (4) Self-assembly film of graphene oxide and polymer on the surface of plugging material: Take 100 ml of the mixed solution and pour it into the slurry cup of the drilling fluid high temperature and high pressure filter loss meter (drilling fluid performance testing instrument), then add the plugging material, and then pressurize it to 2-3 MPa, filter it for 5-20 minutes, take out the plugging material, and dry it naturally for 24-36 hours.
[0040] In the above specific implementation scheme, the plugging material is a granular solid material such as polyurethane sponge, walnut shell, rubber particles, quartz, rock chips, etc. After self-assembly, graphene oxide and polymer will form a thin film on the surface of the particles and coat the surface of the plugging material. The coating layer has good hydrophobic effect.
[0041] In the above specific embodiment, the polymer is an anionic polyelectrolyte such as hydrolyzed polyacrylic acid, hydrolyzed polyacrylamide, etc.
[0042] Furthermore, the high-temperature and high-pressure filter loss instrument in the above specific implementation scheme can be equivalent to a mechanism that can generate a pressure difference and cause filter loss.
[0043] The present invention has the following beneficial effects:
[0044] (1) The plugging material prepared by the method of the present invention has good temperature resistance and will not fail at high temperatures, thus avoiding the occurrence of repeated leakage.
[0045] (2) The plugging material prepared by the method of the present invention has a composite film formed on its surface. The composite film has hydrophobicity, oil resistance and certain mechanical strength, and is easy to disperse in the oil-based drilling fluid without affecting the rheological properties of the drilling fluid. This solves the problem that conventional plugging materials cannot be dispersed in the oil-based drilling fluid, resulting in unsatisfactory plugging effects.
[0046] (3) The plugging material prepared by the method of the present invention has good oil resistance, is not easy to swell, can maintain elasticity in oil-based drilling fluid, has good matching with cracks, and is conducive to deep cracks. At the same time, it can restore its shape after cracking, which is conducive to the implementation of bridging and networking, and has a good plugging effect on various types of leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The contact angle measurement results of the composite film on the surface of the plugging material after modification in Example 3.
[0048] Figure 2 This is a scanning electron microscope image of the cross-section of the composite membrane on the surface of the modified plugging material in Example 2. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0050] The graphene oxide used in each embodiment of the present invention was purchased from Jining LiTe Nanotechnology Co., Ltd., model LN-GP;
[0051] Polyacrylic acid was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0052] Polyacrylamide was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0053] The drilling fluid high-temperature and high-pressure filtration instrument is from Qingdao Haitong Yuanda Instrument Co., Ltd., model GGS42.
[0054] Example 1
[0055] (1) Preparation of GO (graphene oxide) solution: Weigh 1 g of GO solid powder, add 100 g of deionized water into the mixing cup of a high-speed blender, stir at high speed, add the 1 g of GO weighed above into the deionized water in small amounts several times, and stir at high speed at 1200 rpm for 6 h. After stirring, let the GO solution stand for 24 h, take the supernatant, and obtain a GO solution.
[0056] (2) Preparation of polymer solution: 0.05 g of polyacrylic acid was weighed and added in small amounts to a stirring cup containing 50 g of deionized water. The mixture was stirred at 1800 rpm for 5 h using a high-speed stirrer until the mixture was completely dissolved, thereby obtaining a polymer solution.
[0057] (3) Preparation of mixed solution: Mix the prepared GO solution with the polymer solution to obtain a mixed solution.
[0058] (4) Self-assembly film of graphene oxide and polymer on the surface of plugging material: Take 100 ml of the mixed solution and pour it into the slurry cup of the drilling fluid high temperature and high pressure filter loss instrument, then add 20 g of walnut shell particles with a particle size of 5 mm, then pressurize to 2 MPa, filter for 20 minutes, take out the walnut shell particles, and dry them naturally for 36 hours.
[0059] Example 2
[0060] (1) Preparation of GO (graphene oxide) solution: Weigh 2 g of GO solid powder, add 500 g of deionized water into the mixing cup of a high-speed blender, stir at high speed, add the previously weighed 2 g of GO into the deionized water in small amounts several times, and stir at high speed at 1200 rpm for 8 h. After stirring, let the GO solution stand for 24 h, take the supernatant, and obtain a GO solution.
[0061] (2) Preparation of polymer solution: 0.8 g of polyacrylamide was weighed and added in small amounts to a stirring cup containing 100 g of deionized water. The mixture was stirred at 1800 rpm using a high-speed stirrer until the polymer was completely dissolved, thereby obtaining a polymer solution.
[0062] (3) Preparation of mixed solution: Mix the prepared GO solution with the polymer solution to obtain a mixed solution.
[0063] (4) Self-assembly film of graphene oxide and polymer on the surface of plugging material: Take 100 ml of the mixed solution and pour it into the slurry cup of the drilling fluid high temperature and high pressure filter loss instrument, then add 10 g of 5 mm polyurethane sponge particles, and then pressurize to 3 MPa, filter for 5 minutes, take out the polyurethane sponge particles, and dry them naturally for 24 hours.
[0064] Depend on Figure 2 Scanning electron microscope images show that a structurally ordered deposition layer, namely a composite film layer, is formed on the surface of the plugging material.
[0065] Example 3
[0066] (1) Preparation of GO (graphene oxide) solution: Weigh 1.5 g of GO solid powder, add 250 g of deionized water into the mixing cup of a high-speed blender, stir at high speed, add the 1.5 g of GO weighed above into the deionized water in small amounts several times, and stir at high speed at 1200 rpm for 6 h. After stirring, let the GO solution stand for 24 h, take the supernatant, and obtain a GO solution.
[0067] (2) Preparation of polymer solution: 0.4 g of polyacrylamide was weighed and added in small amounts to a stirring cup containing 80 g of deionized water. The polymer solution was obtained by stirring at 1800 rpm using a high-speed stirrer until the polymer was completely dissolved.
[0068] (3) Preparation of mixed solution: Mix the prepared GO solution with the polymer solution to obtain a mixed solution.
[0069] (4) Self-assembly film of graphene oxide and polymer on the surface of plugging material: Take 100 ml of the mixed solution and pour it into the slurry cup of the drilling fluid high temperature and high pressure filter loss instrument, then add 40 g of 5 mm rubber particles, and then pressurize to 2.5 MPa, filter for 10 minutes, take out the rubber particles, and dry them naturally for 30 hours.
[0070] Comparative Example 1
[0071] (1) Preparation of GO (graphene oxide) solution: Weigh 2 g of GO solid powder, add 500 g of deionized water into the mixing cup of a high-speed blender, stir at high speed, add the previously weighed 2 g of GO into the deionized water in small amounts several times, and stir at high speed at 1200 rpm for 8 h. After stirring, let the GO solution stand for 24 h, take the supernatant, and obtain a GO solution.
[0072] (2) Film formation of graphene oxide on the surface of plugging material: 100 ml of GO solution was poured into the slurry cup of the drilling fluid high temperature and high pressure filter loss instrument, and then 10 g of 5 mm polyurethane sponge particles were added. Then, the pressure was increased to 3 MPa, and the filter loss was performed for 5 min. The polyurethane sponge particles were taken out and dried naturally for 24 h.
[0073] Comparative Example 2
[0074] (1) Preparation of polymer solution: 0.8 g of polyacrylamide was weighed and added in small amounts to a stirring cup containing 100 g of deionized water, and stirred at 1800 rpm using a high-speed stirrer until the polymer was completely dissolved, thereby obtaining a polymer solution.
[0075] (2) Film formation of polymer on the surface of plugging material: Take 100 ml of polymer solution and pour it into the slurry cup of drilling fluid high temperature and high pressure filter loss instrument, then add 10 g of 5 mm polyurethane sponge particles, then pressurize to 3 MPa, filter for 5 minutes, take out the polyurethane sponge particles, and dry them naturally for 24 hours.
[0076] Comparative Example 3
[0077] Take 100 ml of clean water and pour it into the slurry cup of the drilling fluid high temperature and high pressure filter loss instrument, then add 10 g of 5 mm polyurethane sponge particles, then pressurize to 3 MPa, filter for 5 minutes, take out the polyurethane sponge particles, and dry them naturally for 24 hours.
[0078] Performance evaluation and testing
[0079] 1. Temperature resistance test
[0080] The plugging material to be tested is heated using a high-temperature roller heating furnace, and then a high-temperature resistance evaluation experiment is conducted based on the mass retention rate.
[0081]
[0082] Wherein, α is the mass retention rate, %; M1 is the mass of the material before hot rolling, g; M2 is the mass of the material after hot rolling, g.
[0083] Table 1. Mass retention rate after hot rolling at 120℃ for 16h
[0084] Serial number The plugging materials prepared in different embodiments Quality retention rate % 1 Example 1 95.2 2 Example 2 94.6 3 Example 3 95.8 4 Comparative Example 1 92.5 5 Comparative Example 2 91.5 6 Comparative Example 3 91.0
[0085] The test results show that the mass retention rate of the plugging materials prepared in the examples after high-temperature hot rolling is greater than that of the plugging materials prepared in the comparative examples, indicating that the plugging materials prepared by the modification method of the present invention have better temperature resistance than the plugging materials not prepared by the preparation method of the present invention.
[0086] 2. Oil resistance test
[0087]
[0088] Wherein, β is the tensile strength retention rate, %; P1 is the tensile strength of the material before immersion, kPa; P2 is the tensile strength of the material after immersion, kPa.
[0089] Table 2. Tensile strength retention after immersion in diesel for 16 hours at 100℃
[0090] Serial number Leakage plugging skeleton materials prepared in different embodiments Tensile strength retention rate % 1 Example 1 82.5 2 Example 2 79.6 3 Example 3 85.1 4 Comparative Example 1 55.7 5 Comparative Example 2 51.3 6 Comparative Example 3 50.2
[0091] The test results show that the tensile strength retention rate of the plugging materials prepared in the examples after being soaked in diesel is greater than that of the plugging materials prepared in the comparative examples, indicating that the plugging materials prepared by the modification method of the present invention have better oil resistance than the plugging materials not prepared by the preparation method of the present invention.
[0092] 3. Mechanical properties test
[0093] The tensile strength of the elastic mesh plugging material is tested with reference to the national industry standard GB / T 6344-2008 "Determination of tensile strength and elongation at break of soft foam polymer materials".
[0094] Table 3. Tensile strength test results
[0095] Serial number Leakage plugging skeleton materials prepared in different embodiments Tensile strength / MPa 1 Example 1 4.1 2 Example 2 3.9 3 Example 3 4.6 4 Comparative Example 1 2.9 5 Comparative Example 2 3.3 6 Comparative Example 3 2.0
[0096] The test results show that the tensile strength of the plugging materials prepared in the examples is greater than that of the plugging materials prepared in the comparative examples, indicating that the mechanical properties of the plugging materials prepared by the modification method of the present invention are better than those of the plugging materials not prepared by the preparation method of the present invention.
[0097] 4. Hydrophobicity test of composite film on the surface of plugging material
[0098] The contact angle of water droplets on the surface of the composite film of the plugging material was measured using a HARKE-SPCA contact angle meter (Beijing HARKE Testing Instrument Factory), and the hydrophobicity of the composite film on the surface of the plugging material in Example 3 was tested and evaluated. According to the modification method of the present invention, the solid particles with a relatively flat surface are modified, and after the composite film is formed on the surface, the contact angle of water droplets on the surface is measured using a contact angle meter. The specific results are shown in the attached Figure 1 .
[0099] from Figure 1 It can be seen that the water droplets are obviously hydrophobic on the surface of the composite membrane.
[0100] 5. Effect of modified plugging materials on rheology of drilling fluid
[0101] The rheological changes before and after adding plugging materials into oil-based drilling fluid were tested.
[0102] Oil-based drilling fluid formula: base oil + CaCl2 (25%) + 2% to 3% emulsifier + 1% to 3% wetting agent + 2% to 3% organic soil + 2% CaO + barite.
[0103] Table 4. Changes in rheological properties of drilling fluids
[0104] AV(mPa·s) PV (mPa·s) YP(Pa) Before adding plugging material 39 32 13 After plugging material is added 42 33 14
[0105] It can be seen that after adding the plugging material of Example 3, the apparent viscosity and plastic viscosity of the drilling fluid do not change much and are within a reasonable range, indicating that the modified plugging material has little effect on the rheology of the drilling fluid.
[0106] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0107] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for modifying a plugging material, characterized in that: The method comprises adopting graphene oxide and anionic polymer to self-assemble into a film on the surface of the plugging material.
2. The modification method according to claim 1, characterized in that: The steps of the modification method include: (1) adding graphene oxide to deionized water, stirring, standing, and taking the supernatant to obtain a graphene oxide solution; (2) adding the anionic polymer in small amounts to deionized water several times, stirring and dissolving, to obtain an anionic polymer solution; (3) mixing the graphene oxide solution with the anionic polymer solution to obtain a mixed solution; (4) Add plugging materials to the mixed liquid, pressurize, filter out, and dry.
3. The modification method according to claim 1 or 2, characterized in that: In step (1), the mass ratio of graphene oxide to deionized water is 1-2:100-500; And / or, in step (1), the stirring rate is 1000-2000 rpm, and the time is 6-8 hours; And / or, in step (1), the standing time is 16 to 24 hours.
4. The modification method according to any one of claims 1 to 3, characterized in that: In step (2), the mass ratio of the anionic polymer to deionized water is 0.05-0.8:50-100; And / or, in step (2), the stirring rate is 1000-2000 rpm and the time is 1-5 hours.
5. The modification method according to any one of claims 1 to 4, characterized in that: In step (3), the mass ratio of the graphene oxide solution to the anionic polymer solution is 1:1 to 1:
4.
6. The modification method according to any one of claims 1 to 5, characterized in that: In step (4), the ratio of the mass of the plugging material to the volume of the mixed liquid is (0.1-0.4) g:1 ml; And / or, in step (4), the pressure after pressurization is 2 to 3 MPa; And / or, in step (4), the filtration time is 5 to 20 minutes; And / or, in step (4), the drying is carried out under natural conditions for 24 to 36 hours.
7. The modification method according to any one of claims 1 to 6, characterized in that: The plugging material is a granular solid material; And / or, the particle size of the plugging material is 0.5 to 5 mm; And / or, the plugging material is selected from at least one of polyurethane sponge, walnut shells, and rubber particles.
8. The modification method according to any one of claims 1 to 7, characterized in that: The anionic polymer is selected from at least one of polyacrylic acid and anionic polyacrylamide.
9. A plugging material obtained by the modification method according to any one of claims 1 to 8, characterized in that: The surface of the plugging material is provided with a graphene oxide and anionic polymer self-assembled composite film layer.
10. Use of the plugging material obtained by the modification method according to any one of claims 1 to 8 in preventing leakage of drilling fluid in oil fields.
Citation Information
Patent Citations
Nano layered calcium carbonate base bionic composite material and synthetic method thereof
CN100567407C
Drilling pressure-bearing plugging agent for oil-gas wells and preparation and application thereof
CN103923627A
Plugging agent for oil-base drilling fluid and preparation method
CN108977181A
Polymer gel composite plugging agent and preparation method thereof
CN111019617A
Carbon-based tackifier as well as preparation method and application thereof
CN111876138A
